Foreword to Ex Novo Volume 4, 2019 - Gori, Maja; Pintucci, Alessandro; Revello Lami, Martina (Ex Novo: Journal of Archaeology, 2019)
The fourth volume of Ex Novo has the pleasure to host Heleen van Londen, Marjo Schlaman, and Andrea Travaglia as guest editors of the special issue titled The Natural and The Cultural. Integrating Approaches in Landscape Heritage Management. This timely collection of peer-reviewed papers and short essays seek to bridge the longstanding gap between natural and cultural heritage when it comes to landscape management. To this end, the editors foster a combined approach to both domains by promoting stronger internal cooperation and the systematic engagement of new forms of integrated heritage with the external world.